Effect of Biofertilizer Dosage and Al Quran Chanting on the Growth and Yield of Red Spinach (Amaranthus tricolor L.) - Wiratmoko, Widi; Turmuktini, Tien; Amalia, Lia (Journal of Innovation and Research in Agriculture, 2024)
This research was carried out from March to April 2023 at Pondok Tahfidz Generasi Robbani Qurani, Cileunyi, Bandung Regency, West Java. The aim of this research is to study the interaction between the dosage of biological fertilizer and the chanting of the Qur'an on the growth and yield of red spinach plants. The design used is a split plot design. Factor I: Chanting the Al-Quran, namely without chanting the Al-Qur'an and with chanting the Al-Qur'an. Factor II dosage of biofertilizer 0 kg ha־ˡ, 4 kg ha־ˡ, 8 kg ha־ˡ, 12 kg ha־ˡ, 16 kg ha־ˡ repeated 3 times. The research results showed that the application of a dose of biological fertilizer and chanting the Al-Quran had an effect on the growth and yield of red spinach plants as indicated by the results of plant height and number of leaves at the age of 30 DAP, and the application of a dose of bio-fertilizer and chanting of the Al-Quran had an effect on the growth and yield of red spinach plants. shown by the high yield of plants and the number of leaves at the age of 30 HST, in plots with Al-Quran chanting with biofertilizer doses of 8 and 16 kg ha־ˡ, so this biofertilizer dose is the best recommendation.